Compliance with needle-use declarations at two Olympic Winter Games: Sochi (2014) and PyeongChang (2018). Issue 1 (15th June 2019) - Schobersberger, Wolfgang; Blank, Cornelia; Budgett, Richard; Pipe, Andrew; Stuart, Mark Campbell
Abstract : Objectives: We describe compliance with the 'IOC Needle Policy' at two Winter Olympic Games (Sochi and PyeongChang) and compare these findings to those of the Summer Olympic Games of Rio de Janeiro. Method: All needle-use declaration(s) (NUD) received during the course of the 2014 and 2018 Olympic Games were reviewed. We recorded socio-demographic data, the nature and purpose of needle use, product(s) injected, and route of administration. Data were analysed descriptively. Results: In total, doctors from 22 National Olympic Committees (NOCs) submitted 122 NUD involving 82 athletes in Sochi; in PyeongChang, doctors from 19 NOCs submitted 82 NUD involving 61 athletes. This represented approximately 2% of all athletes at both Games, and 25% and 20% of all NOCs participating in Sochi and PyeongChang, respectively. No marked differences in the NUD distribution patterns were apparent when comparing the two Winter Olympic Games. The most commonly administered substances were as follows: local anaesthetics, non-steroidal anti-inflammatory drug and glucocorticoids. Physicians submitted multiple NUD for 24% of all athletes who required a NUD. Conclusion: A limited number of NOCs submitted NUD suggesting a low incidence of needle use or limited compliance (approximately 2%). A key challenge for the future is to increase the rate of compliance in submitting NUD. More effective education of NOCs, team physicians and athletes regarding the NUD policy, its purpose, and the necessity for NUD submissions, in association with the enforcement of the appropriate sanctions following non-compliance are needed.